Increasing Mathematical Curiosity Using Simple AI Instruction In Primary School - Usluoğlu, Büşra; Toptaş, Veli (Papanda Publisher, 2025)
The abstract contains a brief description of the purpose: describes the objectives and In recent years, a new system has introduced itself to the world: Artificial intelligence (AI). Artificial intelligence, an active educator, has begun to take its place in our lives every day. Therefore, it has also taken its place in the education and training system. Artificial intelligence, which is also used in mathematics education, has become one of the shaping effects of the future. Therefore, it is important for education to start from a young age. The main purpose of this study is to explain the artificial intelligence system consisting of mathematical data in the language of primary school students and to increase mathematical curiosity with fun activities and applications. For this purpose, forty-five 4th grade students were studied. The study is a mixed-design study including quantitative and qualitative methods. Since the subject of data processing in mathematics was explained in the study, a pre- and post-test of success was applied. In addition, the opinions of the students were analyzed for the activities performed. In the light of the findings obtained from the study, it was observed that the students' mathematical success increased with simple artificial intelligence applications. In addition, the students whose opinions were taken stated that they discovered the relationship of the artificial intelligence system with the subject of data processing in mathematics as a result of the applications performed and that this increased their mathematical curiosity. These applications and evaluations developed suggestions for more artificial intelligence studies, especially in mathematics classes, at the primary school level.